A compensated multi-gap RPC with 2 m strips for the LEPS2 experiment - Watanabe, Kento; Chen, Huangshan (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
We have developed multi-gap resistive plate chambers (MRPCs) with 2.5×200 cm 2 readout strips for the time-of-flight (TOF) detector system of the LEPS2 experiment at SPring-8. These chambers consist of two float glass stacks with 5 gas gaps each, in a mirrored configuration. A time resolution of σ≃80 ps was achieved for any position within a strip (at above 99% detection efficiency), improved to 60 ps after correcting for a relatively small time-charge slewing effect. This latter fact seems to stem from the suppression of modal dispersion, achieved through convenient design choices.